Desenvolvimento de PCR espécie-específico para o diagnóstico da infecção por Brucella ovis e avaliação comparativa de métodos sorológicos - Mariana Noyma Xavier (2009)
The goal of this study was to develop a PCR test targeting specific B. ovis genomic sequences tobe applied in biological samples from rams and to evaluate three serological tests, AGID usingtwo antigens and CF, available in for the diagnosis of ovine brucellosis. Specific primer pairswere designed targeting 12 open reading frames (ORF). Blood, serum, semen, urine, preputialwash, and organs samples were collected from experimentally infected rams through 180 dayspost infection. Moreover, biological samples from eight rams belonging to B. ovis-free flock aswell as 40 semen samples from rams belonging to naturally infected flocks were obtained. Thelimit of detection of this PCR protocol was 102, 10¹,100 CFU/mL for semen, urine and prepucialwash samples, respectively. Similar sensibility and specificity values were obtained by this PCRmethod when compared to bacteriology using the biological samples. Both ID test presentedsimilar sensitivity and specificity values and, both methods were statistically more efficient thanCF test for the serological diagnosis of B. ovis infection. The results clearly indicate that thisfirst specific PCR method is highly efficient for the diagnosis of B. ovis infection in biologicalsamples from infected rams. Additionally, ID should be used, rather than CF, for the serologicaldiagnosis of this disease with the antigens evaluated